Which Food Will You Choose? - Potter, Claire; Busby, Ailie (London : FEATHERSTONE, 2021)
Mum's in a bad mood. She's fed up with all the beige foods in the kitchen, like chicken nuggets, chips, pasta, crisps, cereal - so she's taking her children to the supermarket to play a game. But you can't play a game in the supermarket, can you? Yes you can! This ingenious new book from Claire Potter helps to break down the fussy eating headache by turning choosing new foods into a game. Every day of the week we see two children go to the supermarket and pick food they would like to try - but there is a twist. The food must be a certain colour, chosen by their mum! On Monday she tells them to choose three RED foods, on Tuesday three YELLOW foods, on Wednesday three GREEN foods - What foods will they pick? And how will they eat them? There are so many to choose from - Which ones would YOU pick? And how would YOU eat them?
Keywords: Food -- Juvenile fiction; Children's stories; Picture books